The next hype in social media advertising: Examining virtual influencers’ brand endorsement effectiveness - Kim, Eunjin (Anna); Kim, Donggyu; E, Zihang; Shoenberger, Heather (Frontiers in Psychology, 2023)
Virtual influencers are gaining prominence as a way of attracting people’s attention on social media, but limited research has been conducted on this subject. In this research, we explore the effects of human-like virtual influencers (HVIs) vs. anime-like virtual influencers (AVIs) and sponsorship disclosure on message credibility perception and message attitudes. Conducted with a 2 (virtual influencer type: HVI vs. AVI) x 2 (sponsorship disclosure: absent vs. present) between-subjects experiment, our findings suggest that HVI endorsements produce greater perception of message credibility and message attitudes than AVI endorsements, but the superior effect of HVIs (vs. AVIs) vanishes when sponsorship is disclosed. The results also show that message credibility plays a significant mediating role only when sponsorship is not disclosed. We believe our research offers interesting insights to both researchers and practitioners on the topic of virtual influencers.